CCL5 Induces a Sarcopenic-like Phenotype via the CCR5 Receptor - Francisco Aguirre; Franco Tacchi; Mayalen Valero-Breton; Josué Orozco-Aguilar; Sabrina Conejeros-Lillo; Josefa Bonicioli; Renata Iturriaga-Jofré; Daniel Cabrera; Jorge A. Soto; Mauricio Castro-Sepúlveda; Marianny Portal-Rodríguez; Álvaro A. Elorza; et al. (Antioxidants)
Sarcopenia corresponds to a decrease in muscle mass and strength. CCL5 is a new myokine whose expression, along with the CCR5 receptor, is increased in sarcopenic muscle. Therefore, we evaluated whether CCL5 and CCR5 induce a sarcopenic-like effect on skeletal muscle tissue and cultured muscle cells. Electroporation in the tibialis anterior (TA) muscle of mice was used to overexpress CCL5. The TA muscles were analyzed by measuring the fiber diameter, the content of sarcomeric proteins, and the gene expression of E3-ligases. C2C12 myotubes and single-isolated flexor digitorum brevis (FDB) fibers were also treated with recombinant CCL5 (rCCL5). The participation of CCR5 was evaluated using the antagonist maraviroc (MVC). Protein and structural analyses were performed. The results showed that TA overexpression of CCL5 led to sarcopenia by reducing muscle strength and mass, muscle-fiber diameter, and sarcomeric protein content, and by upregulating E3-ligases. The same sarcopenic phenotype was observed in myotubes and FDB fibers. We showed increased reactive oxygen species (ROS) production and carbonylated proteins, denoting oxidative stress induced by CCL5. When the CCR5 was antagonized, the effects produced by rCCL5 were prevented. In conclusion, we report for the first time that CCL5 is a novel myokine that exerts a sarcopenic-like effect through the CCR5 receptor.